Shell size distributions, land use, and water quality relationships of a freshwater apple snail Pomacea canaliculata (Lamarck, 1822) in Maninjau Lake, West Sumatra, Indonesia - NOVERITA DIAN TAKARINA; TRI RETNANINGSIH SOEPROBOWATI; PUTI SRI KOMALA; LUKI SUBEHI; MARTHA WOJEWÓDKA-PRZYBYŁ; DJABANG NURDIN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Takarina ND, Soeprobowati TR, Komala PS, Subehi L, Wojewódka-Przyby? M, Nurdin D. 2023. Shell size distributions, land use, and water quality relationships of a freshwater apple snail Pomacea canaliculata (Lamarck, 1822) in Maninjau Lake, West Sumatra, Indonesia. Biodiversitas 24: 5478-5484. The freshwater apple snail, Pomacea canaliculata (Lamarck, 1822), is a common mollusk in lake ecosystems, including Maninjau Lake, West Sumatra. Despite its presence in Maninjau Lake, the information about its shell size, land use, and water quality variable relationships is very limited. This paper aims to study how the land use surrounding the lake and water quality variables can affect the shell size distributions of P. canaliculata. The samples were collected from several locations representing the varieties of land uses, including settlements, paddy fields, forest covers, and river mouths, along with water quality variables. Statistical analysis was done using ANOVA and validated by Tukey's post hoc test to analyze differences among locations. Pearson’s correlation test was used to analyze the relationship between shell size and water quality variables. The results show that the differences in land use and water quality variables affected the variations of shell length (P < 0.05, F = 4.925) and width (P< 0.05, F = 12.369) of P. canaliculata. The average shell length was 2.709 cm and 2.022 cm for the width. The large shell size was observed in settlement land uses (P< 0.05), and the small shell was observed in forest and paddy field land uses (P< 0.05). The water near settlement land uses was characterized by high temperatures, while colder water was observed in forest and paddy field land uses. Pearson’s test confirms that increases in shell length and width were correlated with increases in temperature and dissolved oxygen.